Penerapan Prinsip Riba dalam Transaksi Pinjaman Konvensional: Studi Komparasi Fikih Muamalah dan Ekonomi Islam - Muhamat Akhrom (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2026)
This study aims to examine the concept of riba from the perspectives of fiqh muamalah and Islamic economics and to compare it with conventional lending practices in Indonesia, including the use of alternative terms such as service fees, administrative charges, and penalties in digital lending services. This study employs a qualitative descriptive-comparative approach. Primary data were obtained from classical and contemporary fiqh muamalah literature, fatwas issued by the National Sharia Council–Indonesian Ulema Council (DSN-MUI), and national financial regulations, while secondary data were collected from the Financial Services Authority (OJK) and Statistics Indonesia (BPS) for the 2024–2025 period. The findings indicate that any predetermined addition to loan repayment, regardless of its terminology, constitutes riba nasi'ah because it guarantees a fixed return without genuine economic compensation or risk sharing. OJK and BPS data also reveal a persistent structural gap between the conventional and Islamic financial systems. The market share of Islamic banking remained relatively stagnant at approximately 7.4–7.7% of total national banking assets, while the Islamic financial literacy and inclusion indices reached only 43.42% and 13.41% in 2025, considerably lower than the national figures. Meanwhile, conventional financial technology (fintech) lending continued to grow by more than 27% year-on-year. The study concludes that eliminating riba-based practices requires not only compliance with Islamic legal principles but also innovative Sharia financing products and stronger Islamic financial literacy to provide accessible and competitive alternatives to conventional lending